2003
DOI: 10.1212/01.wnl.0000057720.36503.2c
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-release oxycodone for pain in diabetic neuropathy

Abstract: In this 6-week trial, CR oxycodone was effective for the treatment of moderate to severe pain due to diabetic neuropathy. Adverse events were typical of opioid-related side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
229
1
10

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(246 citation statements)
references
References 31 publications
6
229
1
10
Order By: Relevance
“…This may be caused by differences in drug distribution and kinetics between control and diabetic rats that make direct comparisons of systemically delivered drug efficacy difficult to interpret [44], although recent reports indicate that diabetic rats also show impaired function of spinal mu opiate receptors [45]. There is emerging experimental evidence that delta and kappa opioid receptors can provide plausible alternative targets for alleviating painful diabetic neuropathy [46] and recent clinical trials with oxycodone, a mixed mu and kappa opioid receptor agonist [47,48] also support this approach. Asimadoline may provide a local therapeutic approach to treating diabetic painful neuropathy that avoids the sedation and dysphoria occurring with KOR agonists that penetrate the central nervous system [49] and also avoids the respiratory depression and potential for abuse associated with mu opioid agonists [50].…”
Section: Discussionmentioning
confidence: 99%
“…This may be caused by differences in drug distribution and kinetics between control and diabetic rats that make direct comparisons of systemically delivered drug efficacy difficult to interpret [44], although recent reports indicate that diabetic rats also show impaired function of spinal mu opiate receptors [45]. There is emerging experimental evidence that delta and kappa opioid receptors can provide plausible alternative targets for alleviating painful diabetic neuropathy [46] and recent clinical trials with oxycodone, a mixed mu and kappa opioid receptor agonist [47,48] also support this approach. Asimadoline may provide a local therapeutic approach to treating diabetic painful neuropathy that avoids the sedation and dysphoria occurring with KOR agonists that penetrate the central nervous system [49] and also avoids the respiratory depression and potential for abuse associated with mu opioid agonists [50].…”
Section: Discussionmentioning
confidence: 99%
“…Controlled-release oxycodone improved pain scores in two single-center trials in patients with painful diabetic neuropathy, one of which had a small sample size (132,133). It may provide additional analgesia for patients on a2-d ligand treatment (134).…”
Section: Opioid and Atypical Opioid Analgesicsmentioning
confidence: 99%
“…Despite the demonstrated effectiveness of opioids in the treatment of neuropathic pain (15,132,134,135), there is a high risk of addiction, abuse, sedation, and other complications and psychosocial issues even with short-term opioid use. For these reasons, opioids are not recommended in the treatment of painful DSPN before failure of other agents that do not have these associated concerns (136)(137)(138).…”
Section: Warnings On All Opioidsmentioning
confidence: 99%
“…13 In a crossover study comparing 4-week treatment periods, venlafaxine and imipramine were found to be superior to placebo in relieving DPNP. 14 Other drugs reported to manage DPNP are "anticonvulsants," 15,16 selective serotonin reuptake inhibitors, 17 controlled-release oxycodone, 18,19 and the synthetic cannabinoid CT-3. 20 Duloxetine hydrochloride (Cymbalta ® , Eli Lilly and Company, Indianapolis, IN) is a selective 5-HT and NE reuptake inhibitor that is relatively balanced in its affinity for both 5-HT and NE reuptake inhibition.…”
Section: Introduction Dmentioning
confidence: 99%